Funding Cost and Bank Liquidity Creation: Evidence from the U.S. - Dung Viet Tran; Ashraf Khan; M. Kabir Hassan (Asian Academy of Management Journal of Accounting and Finance, 2025)
Recent academic research shows that banks with a high amount of deposits are inclined toward creating more liquidity and taking more risk. However, little is known about the puzzle of liquidity creation and how it is influenced by the cost of funding. This article aims to study the impact of the cost of funding on liquidity creation in the U.S. banking industry. Using comprehensive quarterly data for the period 2001 to 2019, we find that the cost of funding negatively relates to the bank’s ability to create liquidity and the bank creates less liquidity and takes less risk when the cost of funding is high. Moreover, we show that large and public banks are more responsive to depositors’ behaviour, arising from changes in the cost of deposits. Our results are robust to alternative econometric approaches including addressing the endogeneity concerns, the measure of funding cost and liquidity creation, bank size and different crisis periods.